Pressure effects on radiative heat transfer in sooting turbulent diffusion flames. (April 2020) - Nmira, Fatiha; Liu, Yuying; Consalvi, Jean-Louis; Andre, Frederic; Liu, Fengshan
Highlights: Numerical investigation of pressure effects on RHT and TRI in sooting flames. Specific high pressure flames have been designed based on Froude modelling. Two competitive mechanisms affecting the radiant fraction are evidenced. Two competitive mechanisms affecting TRI are evidenced. Abstract: This article investigates the effects of increasing pressure up to 4 atm on radiative heat transfer in momentum-driven methane turbulent jet flames by using well-established chemical mechanism, combustion, soot production and radiation models. A transported PDF method is used to close properly the soot-production turbulence interaction and the emission Turbulence Radiation Interaction (TRI). A Narrow-Band CK (NBCK) model is used as the gas radiative property model. The absorption TRI is neglected based on the Optically-Thin Fluctuation Approximation (OTFA). In accordance with a previous study dealing with non-sooting hydrogen flames (Nmira et al., JQSRT 220 (2018) 172–179), the 3-atm and 4-atm flames are designed from the atmospheric flame by using a Froude modeling approach that allows to preserve the flame/flow structure as the pressure is increased and hence to isolate the pressure effects on soot production, radiative heat transfer, and TRI. The effects of increasing pressure on radiant fraction result from two competing mechanisms: i) an increase in soot emission that tends to increase the radiant fraction and ii) a reduction in flame transparency that tends to reduce it. For the present flames, the first mechanism dominates the second, resulting in an increased radiant fraction with increasing the pressure. The TRI effects on flame radiative loss are also governed by competing mechanisms. The enhancement mechanism is due to gas emission TRI and temperature self-correlation effects on soot emission whereas the reduction mechanism is caused by the negative correlation between soot volume fraction and temperature. The former dominates whereas the latter becomes increasingly important with increasing the pressure. This limits the increase in the global radiative loss due to TRI as the pressure is increased. In addition, numerical simulations show that the TRI effects can reduce the local radiative loss in regions of high soot concentration of the 4 atm flame.